Essential facilities doctrine in European Union Law - Zalewska, Marta (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2013)
Formed at the end of the nineteenth century in the United States, the essential facilities doctrine was created to prevent the refusal of access to certain key equipment, which is used as an instrument to secure the dominant position of the undertaking in those markets where the emergence of competition is strictly related to obtaining access to key device. The author describes the initiation in the 1970’s of the acquisition of the American doctrine by European Union law by focusing on the role of the European Commission and the Court of Justice of the European Union in this process. Both American and European prsemises for an application of the essential facilities doctrine are presented, as well as its advantages and disadvantages.